1996
DOI: 10.1002/kin.2
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of esterification of acetic acid with propyl alcohol by heterogeneous catalysis

Abstract: Kinetic data on the esterihcation of acetic acid with propyl alcohol catalyzed by the ion exchange resin DOWEX MONOSPHERE 650 C have been obtained using a stirred batch reactor It was checked if there is an influence of pore diffusion and film resistance on the reaction rate when varying reaction temperature, initial molar ratios, and amount of resin The possible mechanisms of reaction were mathematically treated using the theories of LangmuirHinshelwood and Rideal-Eley. Taking the nonideal behavior of the sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
34
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 3 publications
7
34
0
1
Order By: Relevance
“…For instance, Song et al [2] and Pöken et al [3] studied the esterification of methyl acetate, and Gangadwala et al [4] investigated the reaction system of butyl acetate. On the other hand, the heterogeneous kinetics of propyl acetate synthesis reaction was less studied; the available two publications [5,6] both reported the reaction kinetics using Dowex-50W as the catalyst. Krishnaiah and Rao [5] reported that the Langmuir-Hinshelwood-HougenWatson (LHHW) model was selected to correlate the experimental data in their work.…”
Section: Introductionmentioning
confidence: 97%
“…For instance, Song et al [2] and Pöken et al [3] studied the esterification of methyl acetate, and Gangadwala et al [4] investigated the reaction system of butyl acetate. On the other hand, the heterogeneous kinetics of propyl acetate synthesis reaction was less studied; the available two publications [5,6] both reported the reaction kinetics using Dowex-50W as the catalyst. Krishnaiah and Rao [5] reported that the Langmuir-Hinshelwood-HougenWatson (LHHW) model was selected to correlate the experimental data in their work.…”
Section: Introductionmentioning
confidence: 97%
“…They have investigated the influence of various parameters and proposed the second order rate equation [19,20]. Meanwhile, the research on the esterification of acetic acid with propyl alcohol over heterogeneous catalyst, Dowex Monosphere 650 C, has been reported [21], where the reaction mechanism was presented, and kinetic and thermodynamic parameters were calculated.…”
mentioning
confidence: 99%
“…Elles concernent près d'une centaine de réactions rassemblées au sein d'une quinzaine de classes différentes. Les réactions d'estérification constituent sans doute la famille de réaction la plus étudiée en distillation réactive (Bart et al, 1996 ;Okasinski et Doherty, 2000 ;Brehelin, 2007 ;Steinigeweg et Gmehling, 2002 ;Grob et Hasse, 2005 ;Lee et al, 2000 ;Tischmeyer et Arlt, 2004 ;Chen et al, 1999 ;Omota et al, 2003). Parmi les autres familles de réaction utilisables en distillation réactive, citons la transestérification (Bonet, 2006 ;Nishihira et al, 2000 ;Shaerfl et al, 2000 ;Lyuben et al, 2004) dont les applications augmentent dans le domaine des solvants verts et du biodiesel; les réactions d'éthérification constituent également un large vivier d'application pour la distillation réactive comme la synthèse du MTBE (Ryu et Gelbein, 2002), du TAME (Kolodziej et al, 2004) ou de l'ETBE; les réactions d'hydratation comme l'hydratation de l'oxyde d'éthylène (Steyer et al, 2002) ou la déhydratation du ter-butanol (Abella et al, 1999).…”
Section: Lettres Et Symbolesunclassified